Canakinumab treatment patterns in sJIA, FMF, TRAPS, and MKD/HIDS: real-world insights from a Belgian non-interventional study - Michel Moutschen; Cécile Boulanger; Joke Dehoorne; Rik Joos; Florence Roufosse; Vito Sabato; Jeroen van der Hilst; Eleonore Maury; Hilde Rabijns; Marijn Witterzeel; Carine Wouters (BMC Rheumatology)
Abstract Background Canakinumab, an IL-1β inhibitor, has demonstrated long-term efficacy and safety in patients with sJIA, FMF, TRAPS, and MKD/HIDS who experience inadequate disease control with conventional treatments. This non-interventional study aimed to gain insights into canakinumab use and treatment patterns for these diseases in Belgium. Methods Between July 1, 2018 and June 30, 2023, this national, non-interventional, retrospective/prospective study enrolled patients aged ≥ 2 years with sJIA, FMF, TRAPS, or MKD/HIDS reimbursed for, and treated with, canakinumab in Belgium. Part 1: retrospective data collection from first canakinumab administration in the initial 6-month reimbursement period until date of study inclusion. Part 2: prospective data collection following study inclusion. Canakinumab treatment and safety data were collected throughout. Results At data cut-off, 96 patients (7 sJIA, 70 FMF, 13 TRAPS, 6 MKD/HIDS) were enrolled, of whom 54.2% were female and 87.5% were adults (aged ≥ 18 years). Median age at first canakinumab administration was 34.0 years (20.0, 35.0, 37.0, and 42.0 years in sJIA, FMF, TRAPS, and MKD/HIDS, respectively). Eighteen patients discontinued treatment (3 sJIA, 11 FMF, 4 TRAPS), which was due to lack of efficacy (per investigator’s judgment) in 10 (10.4%) patients. Median dose per administration was 289.1 mg in patients with sJIA, and 150.0 mg in patients with FMF, TRAPS, and MKD/HIDS, while median interval between two consecutive administrations was 28.0 days. Thirty-five (36.5%) patients with FMF, TRAPS, or MKD/HIDS received ≥ 1 dose increase (≥ 150 mg). No safety events were reported. Conclusions These non-interventional study data highlight that canakinumab treatment patterns are generally aligned with the summary of product characteristics (SmPC) and reimbursement criteria in Belgium and further support the well-tolerated safety profile of canakinumab. However, Belgian reimbursement criteria require long-term glucocorticoids prior to canakinumab therapy; if it were possible to align treatment more closely with EULAR/PReS guidance, which recommends early initiation of anti-IL-1 or anti-IL-6 therapy, glucocorticoid treatment would be limited and improved outcomes for these patients would likely be possible. Clinical trial number Not applicable.